Administration and Supervision of Islamic Education: Financial Administration, Financial Management, Transparency, Accountability, Organization of Madrasah - Darimus Darimus (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Financial administration is an important aspect of managing organizations, educational institutions, and government agencies, as it relates to the processes of planning, organizing, implementing, recording, supervising, and accounting for the use of financial resources. Proper and systematic financial management is necessary to ensure that financial resources are utilized effectively, efficiently, transparently, and accountably in order to support the achievement of organizational goals. Therefore, understanding the fundamental principles of financial administration is essential for organizational managers so that they can perform financial management functions appropriately and responsibly. This article aims to explain the basic concepts of financial administration and their application in various organizational contexts. The method used in this study is a library research method, which involves examining various literature sources such as books, scientific journals, and official documents related to financial administration. The data obtained are then analyzed descriptively to provide a comprehensive overview of the definition, functions, principles, and implementation mechanisms of financial administration in organizational practice. The results of the study show that financial administration includes several important activities, such as budgeting, managing revenues and expenditures, recording financial transactions, preparing financial reports, and conducting supervision and evaluation of budget utilization. In practice, financial administration must be based on the principles of good financial management, including transparency, accountability, effectiveness, efficiency, and responsibility. The application of these principles aims to prevent the misuse of funds, increase stakeholder trust, and ensure that every financial activity is carried out according to the planned objectives. Furthermore, the proper implementation of financial administration also contributes to improving the quality of organizational management, particularly in terms of program planning, decision-making, and the control of operational activities. With a well-structured financial administration system, organizations are able to monitor cash flow more accurately, prepare clear financial reports, and conduct periodic evaluations of financial usage. Ultimately, this helps organizations achieve their goals more effectively and sustainably. In conclusion, financial administration does not merely function as a process of financial recording but also as a management system that supports the optimal utilization of resources. Therefore, every organization needs to understand and consistently apply the principles of financial administration in order to establish good, transparent, and accountable financial governance.